Comparing the Effect of Animal-Rearing Education in Japan with Conventional Animal-Assisted Education - Nakajima, Yuka (Frontiers in Veterinary Science, 2017)
An increasing number of teachers are introducing animals into their class so that pupils foster cognitive, physiological, and social skills through their interaction with animals. Along with such an educational style termed animal-assisted education (AAE), Japanese formal education has also utilized animals for education. Japanese animal-rearing education is unique regarding the following two points: (1) it takes the form of “education through assisting animals” rather than “animals assisting education,” and (2) animal rearing is embedded in formal education. While conventional AAE expects the benefit from the social support of animals, Japanese animal-rearing education expects benefit from nurturing and caring for animals. The present study aims to identify effective methods for using animals for education by highlighting the benefits of Japanese animal-rearing education. An overview of Japanese animal-rearing education is followed by a critical review of empirical studies of conventional AAE and Japanese animal-rearing education. Despite the differences in the educational styles, it was found that both systems commonly help children adapt to school. Additionally, conventional AAE were effective in enhancing cognitive and athletic ability of students and foster social skills, whilst Japanese animal-rearing education enhanced academic knowledge and skills and cultivated sympathy for animals and other people. Furthermore, it was demonstrated that the experience of raising animals affects children’s development for a long time even after children stop raising animals. In order to determine the effect of animal presence at school, however, more empirical studies with various viewpoints are necessary for both styles of education. Concerning Japanese animal-rearing education, the effects of the differences such as the amount of exposure to animals, developmental stage or character of individual children, the types of animals need to be controlled for a more sophisticated examination. Empirical studies show that preadolescence is one of the periods in which animal rearing has the greatest impact on children’s development. It is suggested that through the program of raising school animals, conventional AAE obtains more variety of effects in their interaction with animals.